MicroRNA-155-5p Contributes to 5-Fluorouracil Resistance Through Down-Regulating TP53INP1 in Oral Squamous Cell Carcinoma - Liu, Bowen; Hu, Jingchao; Zhao, Han; Zhao, Li; Pan, Shiyuan (Frontiers in Oncology, 2022)
The anticancer drug 5-fluorouracil (5-FU) resistance is a major obstacle to reducing the effectiveness of cancer treatment, and its detailed mechanism has not been fully elucidated. Here, in 5-FU-resistant human oral squamous cell carcinoma (OSCC) HSC3 cells (HSC3/5-FU), the levels of 21 miRNA candidates were detected and miR-155-5p level increased strikingly in HSC3/5-FU cells compared to HSC3 cells. Compared with HSC3 cells, the HSC3/5-FU cells transfected with miR-155-5p inhibitors decreased 5-FU IC50. Ectopic expression of miR-155-5p in HSC3 and HSC4 cells increased 5-FU IC50, migration and invasion abilities. Seven miR-155-5p target candidates were discovered by miRNA prediction algorithms, and in HSC3/5-FU cells TP53INP1 showed the lowest mRNA expression level compared with HSC3 cells. Ectopic expression of miR-155-5p in HSC3 and HSC4 cells decreased TP53INP1 expression level, and luciferase reporter assay further determined the interference effect of miR-155-5p on TP53INP1 expression. The enhancement of cell viability, migration and invasion by miR-155-5p after 5-FU treatment was reversed by TP53INP1 overexpression. After treatment with 5-FU, HSC3-miR-155-5p tumor-bearing nude mice presented growing tumors, while HSC3-TP53INP1 group possessed shrinking tumors. In conclusion, these results lead to the proposal that miR-155-5p enhances 5-FU resistance by decreasing TP53INP1 expression in OSCC.